Finite element modeling of maximum stress in pelvic floor structures during the head expulsion (FINESSE) study - Cechova, Hana; Kalis, Vladimir; Havelkova, Linda; Rusavy, Zdenek; Fiala, Pavel; Rybarova, Martina; Hyncik, Ludek; Krofta, Ladislav; Ismail, Khaled M (International urogynecology journal, 2021)
INTRODUCTION AND HYPOTHESIS: Several studies have assessed birth-related deformations of the levator ani muscle (LAM) and perineum on models that depicted these elements in isolation. The main aim of this study was to develop a complex female pelvic floor computational model using the finite element method to evaluate points and timing of maximum stress at the LAM and perineum in relation to the birth process. METHODS: A three-dimensional computational model of the female pelvic floor was created and used to simulate vaginal birth based on data from previously described real-life MRI scans. We developed three models: model A (LAM without perineum); model B (perineum without LAM); model C (a combined model with both structures). RESULTS: The maximum stress in the LAM was achieved when the vertex was 9 cm below the ischial spines and measured 37.3 MPa in model A and 88.7 MPa in model C. The maximum stress in the perineum occurred at the time of distension by the suboocipito-frontal diameter and reached 86.7 MPa and 119.6 MPa in models B and C, respectively, while the stress in the posterior fourchette caused by the suboccipito-bregmatic diameter measured 36.9 MPa for model B and 39.8 MPa for model C. CONCLUSIONS: Including perineal structures in a computational birth model simulation affects the level of stress at the LAM. The maximum stress at the LAM and perineum seems to occur when the head is lower than previously anticipated.
Keywords: perineum; Dental Porcelain; Stress; Birth; analýza metodou konečných prvků; Pregnancy; těhotenství; vedení porodu; Perineum; Partum; Pelvic Floor; Tension; Perineal; Levator; Modeling; Delivery; lidé; ženské pohlaví; zubní porcelán; Finite Element Analysis; Humans; Delivery, Obstetric; pánevní dno; Female; Muscle